2011
DOI: 10.1097/brs.0b013e3181f72b94
|View full text |Cite
|
Sign up to set email alerts
|

Human Disc Nucleus Properties and Vertebral Endplate Permeability

Abstract: Study of human cadaveric discs quantifying endplate permeability and porosity and correlating these with measures of disc quality: cell density, proteoglycan content, and overall degeneration. Permeability and porosity increased with age and were not correlated with cell density or overall degeneration, suggesting that endplate calcification may not accelerate disc degeneration.Study Design-Experimental quantification of relationships between vertebral endplate morphology, permeability, disc cell density, glyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
110
2
6

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(145 citation statements)
references
References 66 publications
11
110
2
6
Order By: Relevance
“…It is well recognized that GAG content decreases with degeneration [34]. Additionally, Rodriguez et al [30] found that endplate porosity increases with age, while GAG content, as in our study, decreases. Collectively, the presented findings support the theory that endplate porosity increases with age, and that this may be an adaptive response to a reduction of nuclear swelling pressure.…”
Section: Glycosaminoglycans In the Intervertebral Discs And The Endplsupporting
confidence: 83%
See 2 more Smart Citations
“…It is well recognized that GAG content decreases with degeneration [34]. Additionally, Rodriguez et al [30] found that endplate porosity increases with age, while GAG content, as in our study, decreases. Collectively, the presented findings support the theory that endplate porosity increases with age, and that this may be an adaptive response to a reduction of nuclear swelling pressure.…”
Section: Glycosaminoglycans In the Intervertebral Discs And The Endplsupporting
confidence: 83%
“…Cranial and caudal endplates exhibited similar cell density and GAG content, as was also found by Rodriguez et al [30]. The endplate presented similar cell density throughout all of its structure, in some cases "matching" IVD regions of low cell density with endplate areas of high cell density (e.g.…”
Section: Cell Density In the Intervertebral Disc And The Endplatessupporting
confidence: 80%
See 1 more Smart Citation
“…While for some subjects 2-3 levels were used from a single spine, consistent with common practice in the literature [32][33][34], these discs were assumed to be independent samples and post hoc statistical analysis confirmed no subject dependence on CEP height. Each whole spine was first scanned with a mid-sagittal T2-weighted turbo spin echo imaging sequence for routine grading of degenerative state [25,26].…”
Section: Optimization Of Cep Image Contrastmentioning
confidence: 99%
“…In our study, we have not decided to go beyond microCT and histological analysis, even though some studies [1,20,26] reached out for biochemical parameters to supplement their search for the cause of endplate-IVD degeneration. This is something worth exploring in future studies, as different studies [1,20,26] produce conflicting results -especially when it comes to the role of glycosaminoglycans in the interplay between age, endplate bone porosity and IVD degeneration.…”
Section: Discussionmentioning
confidence: 99%